Postpartum contraception; Maria Auxiliadora Hospital Experience - Pinedo, Adolfo (2015)
We observed a notorious decrease of contraceptive methods users at Maria Auxiliadora Hospital until the third trimester of 1991, in relation to the last four years. Consequently we decided to carry out a prospective study on contraceptive methods administration at the postpartum period from october 1.th, 1991 to December 31.th, 1994. We obtained 51,2% of acceptance: 19,8% medroxiprogesterone, 12,2 IUD, 8% tubal occlussion, 6,0% condom and 2,3% pills. Postpartum acceptance was more than outpatients with p<0,01. Our conclusion is that the postpartum period is a very important moment, with previous information and advise during pre natal control, to administrate not only reversible but also definitive contraceptive methods.